Governing (by) Expertise. The Politics of Social Scientific Knowledge Production - Gengnagel, Vincent; Schmidt-Wellenburg, Christian; Lebaron, Frederic (Serendipities. Journal for the Sociology and History of the Social Sciences, 2026)
This special issue examines the Janus-faced position of the social sciences in modern societies. The social sciences explain and critique social life while simultaneously serving as professions of government embedded in governing, policy-making, and institutional reform. Hence, academic autonomy is never absolute but always relative, negotiated within fields and structured by power. Ultimately, the social sciences are embedded in the very processes they are meant to study. Recognising this immersion calls for collective, socio-historical self-awareness and continually re-negotiating the autonomy of the social sciences in the context of societal heteronomies being integrated into their practice, making reflexivity the distinctive vocation of a relational sociology grounded in methodological pluralism.